Case Study of SMAN 2 Pandeglang Students with High Enthusiasm but Difficult to be Consistent (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Enthusiasm for learning is one of the important indicators of student involvement in the learning process. However, high enthusiasm is not always followed by consistent learning behavior. This study aims to describe the learning enthusiasm of students at SMAN 2 Pandeglang, analyze the causes of students who have high enthusiasm but have difficulty maintaining learning consistency, and identify factors that affect these conditions. This study uses a qualitative approach with a case study design. The subject of the study was a student of class X of SMAN 2 Pandeglang who showed high enthusiasm for learning but was not consistent in his learning habits. Data was collected through observation, interviews, and documentation, with the validity of the data tested through triangulation. The results of the study showed that students had high enthusiasm which was evident from their activeness in class, interest in certain subjects, and involvement in extracurricular activities. However, learning consistency is still low due to internal factors such as unstable time management and concentration, as well as external factors in the form of a learning environment and the use of gadgets. This research confirms that enthusiasm is the initial capital of learning, while consistency is the key to sustainable academic success.